The impact of foreign aid on aggregate welfare measures : a panel data analysis - Alves, José (2018)
Does foreign aid enhance aggregate human welfare? This paper attempts to answer this question by using a panel of twenty-eight countries, covering the period from 1990 to 2014. It explores intra-country variation by splitting the sample into low-income and middle-income countries. Combined with the fixed effects estimator, these approaches sought to control for the heterogeneity of the effects of aid on welfare measures. Perhaps surprisingly, there was no evidence that foreign aid contributes to the reduction of infant mortality or increase of human development index.